“Work With Me, Not For Me”: Malaysia Under Abdullah Ahmad Badawi (2003-2009)” / Sivamurugan Pandian...[et al.] - Pandian, Sivamurugan; Omar, Rusdi; Mohd Sani, Mohd Azizuddin (2010)
This paper examines the political and executive leadership in Malaysia, with reference to the fifth Prime Minister, Tun Abdullah Ahmad Badawi. The Prime Minister is an important autonomous actor, a leader of the government party who also manages public bureaucracy and utmost, Abdullah is seen as the leader of the people. Policy agenda depends on the Prime Minister’s authority to either make an impact or bring changes. This paper will address the leadership style of Abdullah in the executive and policy-making and what kind of influence does he provide in policy-making and its implications in Malaysia’s political environment .